MODEL PENERAPAN MANAJEMEN RISIKO UMKM PADA ERA PANDEMI COVID 19 STUDI KASUS USAHA BATIK TULIS LASEM DI KABUPATEN REMBANG JAWA TENGAH - Damayanti .; Rikah . (STIE Pelita Nusantara Semarang, 2021)
The Covid-19 pandemic has greatly affected the economy and business in Indonesia, including the Lasem Batik Tulis MSMEs as a leading sector in Rembang Regency that requires good risk management. The design of the risk management model is needed by MSMEs Batik Tulis Lasem at this time. This research uses exploratory case studies with qualitative methods and Group Discussion Forums as the methods used to identify risks. This qualitative research used snow ball sampling technique and obtained five respondents. The results of the study show that business risks have been identified and the risk indicators grouping in business uncertainty in the Lasem batik batik MSMEs based on business areas and uncertainties which include customers, supply, infrastructure, finance and the environment. This must be considered in the application of risk management in the lasem batik business in Rembang Regency. Based on the risk assessment based on ISO 31000: 2009, the researcher designed a risk management model in the Lasem batik MSMEs. It is hoped that this risk management model can be used by entrepreneurs of Batik Tulis Lasem in dealing with business and competition problems during the pandemic and post-covid-19 pandemic.